Molecular Mechanisms of Flavonoids against Tumor Gamma-Herpesviruses and Their Correlated Cancers-A Focus on EBV and KSHV Life Cycles and Carcinogenesis - Hassan, Sherif T S; Šudomová, Miroslava (International journal of molecular sciences, 2022)
Epstein-Barr virus (EBV) and Kaposi sarcoma-associated herpesvirus (KSHV) are cancer-causing viruses that belong to human gamma-herpesviruses. They are DNA viruses known to establish lifelong infections in humans, with the ability to develop various types of cancer. Drug resistance remains the main barrier to achieving effective therapies for viral infections and cancer. Thus, new medications with dual antiviral and anticancer actions are highly needed. Flavonoids are secondary metabolites biosynthesized by plants with diverse therapeutic effects on human health. In this review, we feature the potential role of flavonoids (flavones, protoflavones, isoflavones, flavanones, flavonols, dihydroflavonols, catechins, chalcones, anthocyanins, and other flavonoid-type compounds) in controlling gamma-herpesvirus-associated cancers by blocking EBV and KSHV infections and inhibiting the formation and growth of the correlated tumors, such as nasopharyngeal carcinoma, Burkitt's lymphoma, gastric cancer, extranodal NK/T-cell lymphoma, squamous cell carcinoma, Kaposi sarcoma, and primary effusion lymphoma. The underlying mechanisms via targeting EBV and KSHV life cycles and carcinogenesis are highlighted. Moreover, the effective concentrations or doses are emphasized.
Keywords: Neoplasms; Epstein-Barr Virus Infections; anthokyaniny; Herpesvirus 4, Human; Kaposi sarcoma-associated herpesvirus (KSHV); flavonoids; Herpesvirus 8, Human; virus Epsteinův-Barrové; infekce virem Epsteina-Barrové; Epstein–Barr virus (EBV); anticancer properties; Kaposiho sarkom; Carcinogenesis; herpesviruses; tumor viruses; lidé; lidský herpesvirus 8; carcinogenesis; flavonoidy; molecular mechanisms; Humans; karcinogeneze; cancer treatment; nádory; Flavonoids; Anthocyanins; Herpesviridae; Sarcoma, Kaposi; antiviral activities